Population connectivity of the swordtip squid Uroteuthis edulis between southern Japan and northern Taiwan using statolith trace elemental analysis - Pang, Yumeng; Yokoyama, Yusuke; Aze, Takahiro; Irie, Takahiro; Chen, Chih-Shin; Kawamura, Tomohiko; Iwata, Yoko (Frontiers in Marine Science, 2024)
Uroteuthis edulis (Hoyle, 1885) is an Indo-Pacific squid species widely distributing in the western Pacific, and commercially important especially in Japan and Taiwan. It has been suggested that some individuals are possibly transported from the spawning ground in north Taiwan to the coasts of Japan, however, the strength of population connectivity between those areas and its influence on U. edulis population dynamics were unveiled. To understand the U. edulis population connectivity in this area, the correlations between statolith trace elements and abiotic/biotic factors were examined first, and then squid experienced environments were postulated throughout their entire life cycle. Sr/Ca ratio showed a strongly negative correlation with ambient water temperature but no correlation with individual growth rate, suggesting that Sr/Ca ratio can be used to reflect squid experienced temperatures. Most squid caught in the Sea of Japan hatched in the areas having similar water temperature with where Taiwanese squid hatched, that would be off the north Taiwan or even warmer area. Statolith trace elements successfully distinguished the catch locations but not the hatching grounds, implying that hatching grounds of Japan and Taiwan squid were largely overlapped. Thus, we suggest that there is strong population connectivity of U. edulis population between southern Japan and northern Taiwan. As there was no clear evidence for existence of local population hatched in the Sea of Japan in this study, U. edulis population might display a source-sink population dynamics, that is, population in Taiwanese waters and/or further south as the source, and the one in the Sea of Japan as a sink population. As U. edulis should be considered as a metapopulation, collaboration among countries in the northwestern Pacific is required for sustainable fishery management of this species.